Etyka pracy leśnika w latach 1918–1939 na terenie Wielkopolski w świetle materiałów archiwalnych - Kowalski, Piotr (Annales. Etyka w Życiu Gospodarczym, 2011)
Ethical principles concerning foresters were presented in this article in the light of the forest law passed in the interwar period for the whole country, as well as in the light of the documents issued by the local forest administration. For analysis were submitted especially archive documents on foresters’ responsibility for forest goods: wood and game. Ethical attitude of foresters translated, among other things, into efficient functioning of forest management all over Greater Poland.